Professional Development and Reflective Practice as Tools to Improve Teaching Practice - Carrillo López, Isabel; López Larrea, María (Revista de la Facultad de Contaduría y Ciencias Administrativas; Vol. 1 Núm. 1 (2016): Revista de la Facultad de Contaduría y Ciencias Administrativas, 2017)
This article presents two topics related with the importance of improving teaching practice, one as a social matter and the second as a personal reflection. With both concepts, teachers  have the opportunity to be aware of what is actually happening inside their classrooms in order to make the necessary changes to raise students´ performance and acquisition of knowledge. The topic of professional development introduces structural features and core features as characteristics that teachers ought to follow. The topic of reflective practice presents the guided reflection as one option to analyze teaching performance.